Prevalence of Anxiety Disorders Among Adolescents: A Cross-Sectional Study in An Urban Area of Delhi, India - Febida BPK; Akshithanand KJ; Kumar, Rajesh; Lal, Panna; Banerjee, Bratati (National Journal of Community Medicine, 2025)
Background: Adolescence is a critical period and anxiety disorders affect one in seven adolescents globally, yet data on this in the Indian population remain limited. This research aimed to study the prevalence and types of anxiety disorders among adolescents in an urban area of Delhi. Methods: In this cross-sectional study involving 300 adolescents, participants were selected using systematic random sampling. Data was collected using a pretested semi-structured questionnaire after ethical approval was obtained. Results: The majority were 10-14 years of age (52.7%), with a mean age of 14.35±2.80. The prevalence of anxiety disorders was 35.3%, with social anxiety (14%) being the most common. Prevalence was higher in females and in the 15-19 years age group. Conclusion: This study reveals a significant burden of anxiety disorders (35.3%) among urban adolescents in Delhi, with social anxiety being the most prevalent type.